1994
DOI: 10.1038/bjc.1994.162
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence for low-density lipoprotein receptor-mediated uptake of benzoporphyrin derivative

Abstract: Summary Plasma lipoproteins, such as low-density lipoprotein (LDL), have been proposed to enhance the delivery of hydrophobic photosensitisers to malignant tissue since tumour cells have been shown to have increased numbers of LDL receptors. We have investigated the role of this receptor in the cellular accumulation of the photosensitiser benzoporphyrin derivative (BPD). We observed that: (1) [`4C]BPD-LDL accumulation by LDL receptor-negative fibroblast cell lines was insignificant compared with normal cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(79 citation statements)
references
References 39 publications
2
71
0
3
Order By: Relevance
“…This selectivity may be related to the increased accumulation of BPD by tumour endothelial cells with high levels of low-density lipoprotein (LDL) receptors (Allison et al, 1994) or the rapid internalization of agents bound to the LDL receptor on proliferating endothelial cells compared to quiescent endothelial cells (Fielding et al, 1979). Cells with increased phagocytotic activity, such as injured vessel wall in atherosclerotic vessels, have been shown to accumulate BPD at levels in excess of surrounding microvasculature (Allison et al, 1997) and this may play a role in tumour microvasculature as well.…”
Section: Discussionmentioning
confidence: 99%
“…This selectivity may be related to the increased accumulation of BPD by tumour endothelial cells with high levels of low-density lipoprotein (LDL) receptors (Allison et al, 1994) or the rapid internalization of agents bound to the LDL receptor on proliferating endothelial cells compared to quiescent endothelial cells (Fielding et al, 1979). Cells with increased phagocytotic activity, such as injured vessel wall in atherosclerotic vessels, have been shown to accumulate BPD at levels in excess of surrounding microvasculature (Allison et al, 1997) and this may play a role in tumour microvasculature as well.…”
Section: Discussionmentioning
confidence: 99%
“…A Phase I/II study has been conducted for 21 patients with DME unresponsive laser photocoagulation and demonstrated central macular edema measured by OCT showed a reduction from baseline exceeding 59% at 3 months after injection of RETAAC, which remained at 6 and 12 months, but significant improvement of visual acuity was not achieved. [151]. In addition, it is reported that liposomes composed of negatively charged phospholipids, such as phosphatidylglycerol, uptake into tumor cells by LDL receptor-mediated endocytosis [152].…”
Section: Nt-501mentioning
confidence: 99%
“…The elevated number of LDL receptors expressed on tumour cells has been exploited for the delivery of lipophilic drugs. Allison et al (1994) described the tumour targetting of photosensitizers using LDL as drug carriers and van Berkel et al (1996) used a lipid emulsion mimicking lipoprotein particles loaded with a lipophilic antiviral drug for increased liver uptake.…”
mentioning
confidence: 99%